Análise espacial da razão de aporte de sedimentos na bacia hidrográfica do Rio Seridó, RN-PB - Rabelo, Davi Rodrigues (2018)
The present research sought to evaluate the hydro-sentimentological aspects of the Seridó River Basin (RN-PB, 10 thousand km²) in order to understand how erosion occurs and, subsequently, how sediment is transported throughout the basin. Primary and secondary data were applied to elaborate thematic maps, was elaborated a theoretical-methodological review of the object, being also used remote sensing in addition to geostatistical methods and sedimentological modeling. Estimating the gross erosion, the Universal Soil Loss Equation (EUPS) was applied to the 1992-2015 period. Calculation of the sediment yield ratio (SDR) and its respective sediment yield was done by applying the Maner equation with the EUPS equation. Several river sections within the basin were selected in order to estimate the sediment yield of the basin limited by that section. With this, it was possible to spatially interpolate the variables of interest for the whole basin.Maps were generated for rain erosivity, soil erodibility, topographic factor, use factor and soil cover. This information allowed the parameterization of the EUPS, which synthesizes the mean gross erosion of the basin. According to the results, the average gross erosion of the basin is 29 ton.ha-1.yr-1, but at some critical points, the gross erosion exceeds 100 ton.ha-1.yr-1. The SDR of the Seridó River Basin is 8%, a level compatible with that of other basins of the Brazilian Semi-Arid zone. The sediment yield in the basin outlet was estimated at 2.5 ton.ha-1.yr-1, a value compatible with measurements carried out in Ceará in basins of the same scale. As to the sediment yield along the fluvial channels in high, medium and low course, positive allometry was identified for areas of up to 60 km². On the globe, this pattern is rare for non-glacier regions; being this identification by itself a relevant scientific contribution of the present research. However, as this trend was obtained through hydrosedimentological modeling (and not through long term measurements), it cannot be conclusively stated that the basin has positive allometry. The applied methodology allowed, therefore, a temporal and spatial evaluation of the sediment production in the basin. It is hoped that works of this nature will aid in the understanding and investigation of fluvial geomorphology, environmental planning and harmonious coexistence with the semi-arid environment.